Parasitismo de Meloidogyne spp. em plantas nativas do oeste paranaense e variabilidade genética de populações de Meloidogyne incognita raça 3 - Antes, Vanessa Aparecida (2008)
The aim of this work was to study the parasitism of Meloidogyne incognita on native plants from Western Paraná, Brazil, as well as to assess the genetic variability among different populations belonging to the race 3 of this nematode by RAPD technique. Natural infection was studied in thirty six native plant species, which were identified on the basis of the perineal pattern from mature females and esterase phenotype. Native species that showed no infestation on the root system were inoculated with 1.000 eggs and/or J2 of M. incognita. After 60 days, the inoculated plants were evaluated regarding the number of galls and the number of eggs/or J2 per root. The genetic variability from different single female populations of M. incognita race 3 was studied by RAPD technique, having been tested 10 primers. The native plants that were susceptible to M. incognita parasitism were Rabo-de-Bugio (Lonchocarpus muehlbergianus Hassl.), Ipê Roxo (Tabebuia impetiginosa Mart. Ex DC. Standl), Sanga D água (Croton urucurana Boill), Ipê Amarelo (Tabebuia ahrysotricha Mart ex DC. Standl.), Genipapo (Genipa americana L.), Ariticum Comum (Rollinia mucosa (Jacq.) Baill.) and Aroeira Vermelha (Schinus terebinthifolius Raddi.). On the other hand, M. javanica was found parasiting Café de Bugre (Cordia ecalyculata Vell.), Guatambu Vermelho (Aspidosperma subincanun Mart.) and Tarumã Branco (Cytrarexllum myruanthum Cham.). The DNA polymorphism showed that there was genetic variability among populations from a same race (3) of M. incognita, allowing the separation of them into five genetic groups, through reactions with the primers (O)AK20, A10, AQ12, AS08 and (OP)F01